Staff Emotional Support at Montefiore Medical Center During the COVID-19 Pandemic - Bernstein, Carol A. (Jt Comm J Qual Patient Saf, 2021)
CONTEXT: During the COVID-19 pandemic, frontline workers have experienced high levels of stress and anxiety. Montefiore Medical Center recognized the urgent need for mental health support to mitigate and treat psychological distress among staff. Various mental health support services were implemented. This report provides an overview of the interventions implemented at Montefiore and provides preliminary insights on the utilization and value of these ongoing services. OUTCOMES: The interventions instituted at Montefiore included psychoeducational resources, a phone support line, Staff Support Centers (SSCs), a clinical treatment program, team support sessions, peer support outreach, mental health and wellness programs, and clergy support. The most heavily used service during the pandemic were the SSCs, and the least used service was the clergy support. INSIGHTS: With institutional encouragement and the collective efforts of more than 150 mental health professionals and other staff, it was possible to set up durable mental health supports with multiple points of access. Although many services were available to both clinical and nonclinical staff, outreach was primarily to clinical staff. Additional efforts in the future are needed to more fully reach nonclinical frontline workers. NEXT STEPS: The organization's next steps include evaluation of emotional health and distress among clinical and nonclinical staff using validated self-report measures administered over multiple time intervals. Lessons learned about staff support during COVID-19 will also be integrated into future efforts to support staff well-being more broadly.